The Effects of the Financial Crisis on Cooperative Banks in Europe – A Critical Comparison – - Klaus Henselmann; Dominik Ditter; Philipp Lupp (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2016)
The financial crisis has highlighted the necessity of discussions on the adequacy of banking regulation and accounting standard-setting for financial institutions. We compare the development of several variables in this context between commercial banks, cooperative banks and savings banks from 2005 through 2013, in order to investigate whether smaller banks such as cooperative banks or savings banks tended to be more robust to the financial crisis. We find that the volume of lending (loan loss provisioning) remained stable or increased (decreased) for smaller financial institutions. Furthermore, there is no significant increase in loss avoidance behavior specifically for cooperative banks. Cooperative banks are also the group of banks that showed the least pro-cyclical effects and the most income smoothing behavior. Our results suggest that cooperative banks were the group of banks being most stable during the years surrounding the financial crisis in 2007/2008. This demonstrates the importance that policy makers consider the broad range of financial institutions for discussions on policy adjustments. – – Die Finanzkrise hat gezeigt, dass die Adäquanz der aufsichtsrechtlichen Regeln und der Rechnungslegung von Banken diskutiert werden muss. Wir untersuchen die Entwicklung von Genossenschaftsbanken, Sparkassen und (anderen) Geschäftsbanken von 2005 bis 2013 um herauszufinden, ob kleinere Institute wie Genossenschaftsbanken und Sparkassen in der Krise robuster waren. Es zeigt sich, dass das Kreditvergabevolumen der kleineren Banken stabil blieb oder anstieg. Die Kreditwertberichtigungen sanken. Genossenschaftsbanken zeigten das am wenigsten prozyklische Verhalten und die stärkste Gewinnglättung. Unsere Ergebnisse legen nahe, dass die Genossenschaften die stabilste Bankengruppe in der Finanzkrise 2007/2008 bildeten. Dies sollte bei einer Veränderung aufsichtsrechtlicher Rahmenbedingungen beachtet werden.
Keywords: M41; M48; G21; G28; G18; 330; Cooperative Banks; Financial Crisis; Loan Loss Provisioning; IFRS